In The Red The Politics of Public Debt Accumulation in Developed Countries - Barta, Zsófia (University of Michigan Press, 2018)
Why do rich countries flirt with fiscal disaster? Why did affluent countries â€" like Belgium, Greece, Italy or Japan â€" persistently accumulate so much debt between the 1970s and the 2000s, in times of peace and prosperity, that they became vulnerable and exposed themselves to the risk of default? In the past three decades, an extensive scholarly consensus emerged around the view that the answer is fiscal indiscipline, the lack of sufficient concern for budgetary constraints from policy makers as they try to please voters. ZsÃ³fia Barta argues that explaining why some countries accumulate substantial amounts of debt for decades hinges on understanding the conditions required to allow policy makers to successfully put into place painful adjustment measures.